Varroa Disease in Honey Bees (Eurasian Journal of Research, Development and Innovation, 2024)
Varroa is one of the most prominent pests that infect honey bees in the world. Its infestation causes direct and indirect losses that ultimately lead to the loss of honey bee colonies, unless it is treated. Its infestation losses exceed the losses of all honey bee pests combined. This research aims to study the cleaning behavior of honey bees raised under Wadi Doan conditions. To benefit from it in integrated management, Varroa is a type of animal belonging to the Varroa genus of the Varroa species. The size of this species is small and can be seen with the naked eye. It is dark brown in color and has a flat oval shape. The Varroa destructor mite lives as an external parasite between the abdominal rings of males or bee larvae and feeds on the bee (hemolymph) by creating a wound in the bee’s body with its mouth parts and then applying pressure on the edge of the chink. And it absorbs blood. The Varroa mite walks zigzagging like a crab, with short stops. It does not like light and hides in the cells if it is exposed to it.